Cobalt nanoparticle-catalysed N-alkylation of amides with alcohols - Ma, Rui; Gao, Jie; Zhang, Lan; Wang, Ning; Hu, Yue; Bartling, Stephan; Lund, Henrik; Wohlrab, Sebastian; Jagadeesh, Rajenahally V; Beller, Matthias (Green chemistry, 2024)
A protocol for efficient N-alkylation of benzamides with alcohols in the presence of cobalt-nanocatalysts is described. Key to the success of this general methodology is the use of highly dispersed cobalt nanoparticles supported on carbon, which are obtained from the pyrolysis of cobalt(ii) acetate and o-phenylenediamine as a ligand at suitable temperatures. The catalytic material shows a broad substrate scope and good tolerance to functional groups. Apart from the synthesis of a variety of secondary amides (>45 products), the catalyst allows for the conversion of more challenging aliphatic alcohols and amides, including biobased and macromolecular amides. The practical applicability of the catalyst is underlined by the successful recycling and reusability.